Avicennia marina (Forks.) Vierh. fruit crude extract in a phenotypic screening as a potential Wnt signalling pathway suppressor - Balero, Jomari D.; Ricarte, Marjhun A. (2017)
Several embryonic processes are controlled by different signalling cascades such as Wnt signalling pathway. Nonetheless, mutation of this pathway, which is targeted recently by researchers for inhibition, will develop into different diseases such as colorectal cancer. In this study, a phenotypic screening was done in which Avicennia marina fruit extract was proven effective as a potential inhibitor of the signalling pathway with zebrafish (Danio rerio) as the model organism. Embryos, after 4.3 hours post-fertilization were used and exposed to 300 mM LiCl to imitate Wnt pathway mutation which results to eyeless phenotype. Exposed embryos were then treated with 50 and 100 ug/mL crude extracts from parts of the selected mangroves at 4.7 hpf. After 24 hpf, presence or absence of eyes were recorded and developmental defects were observed after 48 hpf. After application of extracts, one proved effective, which is the fruit extract from A. marina. No dead and less defected embryos were provided by 50 ug/mL fruit extract while the 100 ug/mL rescued more embryos and had lesser eyeless embryos. Developmental defects were also observed such as heart edema and bent tail. Isolation and characterization of the active compounds present in the positive candidate is recommended to be able to determine the possible cause of its inhibitory activity.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.